Ultrasonographic target appearance due to renal calculi containing gas in emphysematous pyelitis - Kiris, Adem; Ozdemir, Huseyin; Bozgeyik, Zulkif; Kocakoc, Ercan (Elsevier BV, 2004)
Emphysematous pyelitis is a rare infection of urinary collecting system due to gas forming bacteria. We present a 43-year-old female patient with emphysemotous pyelitis in a horse-shoe kidney with gas-containing calculi. © 2004 Elsevier Ireland Ltd. All rights reserved.
Keywords: Emphysematous pyelitis; Gas containing calculi